A REVIEW OF MEDICINAL PLANTS USED BY THE BASOTHO FOR TREATMENT OF SKIN DISORDERS: THEIR PHYTOCHEMICAL, ANTIMICROBIAL, AND ANTI-INFLAMMATORY POTENTIAL - Moteetee, A.; Kose, L. Seleteng (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: While the incidence of skin diseases is high in developing countries, they are not regarded as priority due to low mortality rates, however, they are a major concern due to their co-occurrence with HIV/AIDS. Due to lack of accessibility to healthcare facilities and unaffordability of conventional medicines, many people in rural areas resort to medicinal plants. The aim of the study is to document the plants used for treating skin afflictions by the Basotho people residing in Lesotho and the Free State Province of South Africa. Materials and Methods: A comprehensive survey of existing ethnobotanical literature including numerous books was carried out. Electronic databases such as Google Scholar, PubMed, and ScienceDirect were also used to obtain information on the antiinflammatory, antimicrobial, and phytochemical activities of the medicinal plants. Results and discussion: 57 plant species are utilised for the treatment of various skin ailments with a majority of them used for wounds (26 species) and venereal sores (19 species). The plants are distributed in 39 families with the Asteraceae being the most represented with seven species, followed by Solanaceae and Asphodelaceae with four species each. 38 species have previously been evaluated for their phytochemical properties, 40 for their anti-microbial potential, while 29 have been assessed for their antiinflammatory activity. Of the 57, 13 species have not been evaluated for any of the three categories. Conclusion: Many of the plants have been shown to have anti-microbial, anti-inflammatory, and phytochemical properties, which then validates their traditional use.